PENINGKATAN HASIL BELAJAR MENGGUNAKAN MODEL PEMBELAJARAN FLIPPED CLASSROOM BERBANTUAN MEDIA VIDEO PADA SISWA KELAS 4 SEKOLAH DASAR - Mey Pujilestari; Cerianing Putri Pratiwi; Hartini Hartini (Prosiding Konferensi Ilmiah Dasar, 2022)
Based on observations on learning at SDN 02 Pangongangan, Madiun City, problems were found, including the time for studying at school was very limited, only a few hours. This has an impact on student learning outcomes which are low, namely only 5 students or 20% who achieve the KKM score and 20 students get a score below the KKM. The KKM value set is 75. Therefore, the authors make efforts to improve learning so that learning outcomes can increase by using the Flipped Classroom learning model assisted by video media. The implementation of learning improvement actions is carried out by referring to the CAR research procedure, which starts from planning, implementing, observing, and reflecting. The subjects in this study were grade 4B students at SDN 02 Pangongangan, Madiun City, totaling 26 students with 14 male students and 12 female students. In analyzing the data of student learning outcomes using qualitative and quantitative analysis techniques. The research data in cycle 1 has increased by 10 students or 40% of achieving the KKM score. In cycle 2, student learning outcomes have increased to 22 students achieving the KKm or 88%. Based on the results of the study, it can be concluded that classroom action research with the aim of improving learning by using the video-assisted Flipped Classroom learning model can improve students' thematic learning outcomes of theme 9 sub-theme 2 learning 2 in grade 4B students of SDN 02 Pangongangan, Madiun City.